Menyiapkan Pendidikan Muslim Polity Berorientasi Sosio Multikultural di Era Revolusi Industri 4.0 - Syamsuar, Syamsuar; Reflianto, Reflianto (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper aims to set up Islamic education in the perspective of Muslim polity socio-multikultural –oriented in the industrial revolution era of 4.0 while maintaining Islamic values ​​are moderate and peaceful in the Islamic education curriculum in Indonesia. This study reveals the importance of a positive correlation between education and Muslims behavior in order to remain within the norm of life conducive socio multikultural. Preparation of Muslim polity education in the industrial revolution era can be constructed through Islamic socio-multikultural education strategies and integrated character education by online learning. Preparation of this educational model built through cooperative and collaborative learning. implement seamless learning models that allow the role of society and technology synergy to childbirth the education Muslim polity capable of instilling values ​​into the moderate living society of Muslims in Islamic schools, master of science and technology without losing sight of the values ​​of socio multikultural to the pluralistic Indonesian nation. Implementation of this idea can give the two sides to be achieved that is shaping the personality of Indonesian Muslims were cultured based divinity mighty one, moderate,, respect to civilized human values and mastering technology towards an advanced Muslim society in the field of science and technology through the cultivation of rahmatan lil alamin's character in the high Muslim cultural life